Analisis Kata Tabu dan Klasifikasinya di Lirik Lagu Eminem pada Album `The Marshal Mathers LP` - Laily Nur Affini (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2017)
This research is dedicated for readers in the field of linguistics and has a purpose to reveal taboo words based on a certain theory and the classifications. The analysed taboo words exist in Emeninem’s album,The Marshall Mathers LP. A theory employed in the analysis is using TimothyJay theory where taboo words are differentiated in seven classifications; cursing, profanity, blasphemy, obscenity, sexual harassment, vulgar language, name-calling and insult.The data was taken into two parts, primary and secondary. The primary data is the lyric itself and the secondary data is taken from books, articles and dictionary. The result of the analysis shows a revelation of the taboo words classifications, shown up in a table.